2012
DOI: 10.1007/s10459-012-9349-0
|View full text |Cite
|
Sign up to set email alerts
|

Visualising the invisible: a network approach to reveal the informal social side of student learning

Abstract: World-wide, universities in health sciences have transformed their curriculum to include collaborative learning and facilitate the students’ learning process. Interaction has been acknowledged to be the synergistic element in this learning context. However, students spend the majority of their time outside their classroom and interaction does not stop outside the classroom. Therefore we studied how informal social interaction influences student learning. Moreover, to explore what really matters in the students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
248
5
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(281 citation statements)
references
References 52 publications
21
248
5
7
Order By: Relevance
“…Although we added self-reported data from a range of learning disposition instruments to get a more fine-grained, nuanced understanding of the data, several studies indicate that students increasingly use informal networks (Agudo-Peregrina et al, 2014;Hommes et al, 2012) and learning tools (e.g., Facebook, twitter, texts) to share knowledge and learn together. For example, Hommes et al (2012) found that informal social learning links primarily predicted academic performance amongst 300 medical students. Using dynamic social network analyses, Author B (2014) found that 30-80% of learning occurred outside formally assigned groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although we added self-reported data from a range of learning disposition instruments to get a more fine-grained, nuanced understanding of the data, several studies indicate that students increasingly use informal networks (Agudo-Peregrina et al, 2014;Hommes et al, 2012) and learning tools (e.g., Facebook, twitter, texts) to share knowledge and learn together. For example, Hommes et al (2012) found that informal social learning links primarily predicted academic performance amongst 300 medical students. Using dynamic social network analyses, Author B (2014) found that 30-80% of learning occurred outside formally assigned groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, a large body of research (e.g., Borgatti & Cross, 2003;Hommes et al, 2012;Katz et al, 2004) has found that SNA techniques provide a robust predictor for actual social networks and AD programmes in particular (Rienties & Kinchin, 2014;Van Waes et al, Forthcoming), especially given our high response rates (88%) and the triangulation of the results.…”
Section: Limitations and Future Researchmentioning
confidence: 97%
“…As argued by several researchers Moolenaar et al, 2012;Rienties & Kinchin, 2014;Roxå et al, 2011), SNA techniques may allow academic developers and researchers to make these complex relations visible. The question-stem of a SNA questionnaire has a substantial influence on the types of social networks a researcher can explore (Hommes et al, 2012;Katz et al, 2004). According to Hommes et al (2012), friendship networks explore passive information exchange between people, while working and learning networks in an AD context explore the (in)formal communication about teachingrelated activities.…”
Section: The Role Of (In)formal Academic Development On Social Networkmentioning
confidence: 99%
See 2 more Smart Citations